Isolation and characterization of methicillin-resistant Staphylococcus aureus phage SPB against MRSA planktonic cells and biofilm - Ma, Lan; Liu, Yingyu; Zheng, Xiaofeng; Zheng, Baili; Cheng, Yaling; Cai, Yuxuan; Li, Yongchao; Zhang, Wei (Frontiers in Microbiology, 2025)
Methicillin-resistant Staphylococcus aureus (MRSA) is a common antibiotic-resistant pathogen. MRSA and its biofilm pose a great threat to the food industry. In this study, we characterized the biological properties and antibacterial efficacy of phages through the double-layer plate method, transmission electron microscopy (TEM), whole-genome sequencing (WGS), bioinformatic analyses, fluorescence microscopy, and biofilm eradication assays. The results demonstrated that phage SPB is a virulent member of the genus Kayvirus (subfamily Twortvirinae), exhibited a broad host range spanning Staphylococcus species. It effectively lysed 97.3% (36/37) of clinical MRSA isolates and 100.0% (10/10) of coagulase-negative staphylococci strains tested. The optimal multiplicity of infection (MOI) was determined to be 1, with a latent period of 10 min. Environmental stability assays revealed that phage SPB maintained infectivity across temperatures ranging from 4°C to 50°C and pH values between 4 and 11. Genomic analysis showed that phage SPB possesses a 143,170 bp genome with a G+C content of 30.2%, encoding 218 putative coding sequences (CDSs), 3 tRNAs, and no virulence factors were identified through in software screening. Phage SPB exhibited potent inhibition of planktonic bacterial growth. Furthermore, at varying multiplicities of infection (MOIs), it significantly suppressed biofilm formation and eradicated pre-existing biofilms, with statistical significance (P < 0.001). These results suggest that phage SPB can be used as a potential antimicrobial agent to prevent and remove MRSA and its biofilm from food processing.